Pengaruh Media Sosial Terhadap Minat Beli Konsumen (Studi Kasus Toko Sembako May Snack, Kec. Gedeg, Kab. Mojokerto) - Hendriwati, Dea Novita; Rahayu; Hidayat, M. Syamsul (Philosophiamundi, 2024)
Digital development in this era is very rapid, social media has become an important tool in marketing strategies, including in the retail industry. This study aims to analyze the effect of social media on consumer buying interest at MaySnack Grocery Store, Gedeg, Batan Krajan, Mojokerto Regency, using quantitative methods with 127 respondents. The results showed that TikTok Shop has a positive and significant influence on consumer buying interest, with a regression coefficient of 0.658 and a t-test value of 7.223. In addition, Facebook Shop also has a significant effect with a regression coefficient of 0.163 and a t-test value of 4.641. This study also found that the two social media platforms, together, significantly influence consumer purchase intention with a calculated F value of 26,674. In conclusion, the use of TikTok Shop and Facebook Shop as promotional media is effective in increasing consumer buying interest, with TikTok Shop as the most dominant variable. These results provide insight for businesses to optimize their digital marketing strategies to reach a wider and more diverse target market